Vascular Endothelial Growth Factor (VEGF), Mast Cells and Inflammation. (April 2013) - Shaik-Dasthagirisaheb, Y.B.; Varvara, G.; Murmura, G.; Saggini, A.; Potalivo, G.; Caraffa, A.; Antinolfi, P.; Tetè, S.; Tripodi, D.; Conti, F.; Cianchetti, E.; Toniato, E.; et al.
Vascular endothelial growth factor (VEGF) is one of the most important inducers of angiogenesis, therefore blocking angiogenesis has led to great promise in the treatment of various cancers and inflammatory diseases. VEGF, expressed in response to soluble mediators such as cytokines and growth factors, is important in the physiological development of blood vessels as well as development of vessels in tumors. In cancer patients VEGF levels are increased, and the expression of VEGF is associated with poor prognosis in diseases. VEGF is a mediator of angiogenesis and inflammation which are closely integrated processes in a number of physiological and pathological conditions including obesity, psoriasis, autoimmune diseases and tumor. Mast cells can be activated by anti-IgE to release potent mediators of inflammation and can also respond to bacterial or viral antigens, cytokines, growth factors and hormones, leading to differential release of distinct mediators without degranulation. Substance P strongly induces VEGF in mast cells, and IL-33 contributes to the stimulation and release of VEGF in human mast cells in a dose-dependent manner and acts synergistically in combination with Substance P. Here we report a strong link between VEGF and mast cells and we depict their role in inflammation and immunity.